High-resolution clonal mapping of multi-organ metastasis in triple negative breast cancer - Gloria V. Echeverria (Nature Portfolio, 2018)
It is unclear how intra-tumoral heterogeneity contributes to metastasis. Here the authors study the clonal dynamics of triple negative breast cancer metastasis using patient derived xenografts and demonstrate that primary tumor clones harbor properties that support seeding and colonization of multiple organs.